KESIAPAN PRA-NIKAH DITINJAU DARI PERSPEKTIVE BIMBINGAN DAN KONSELING KELUARGA: TINJAUAN LITERATUR - Adellia Ezadany (Jurnal Keluarga Sehat Sejahtera, 2025)
Premarital counseling plays an important role in preparing prospective couples to build a harmonious and resilient family life. This study aims to examine the role and effectiveness of premarital counseling in enhancing marriage readiness and supporting the formation of a sakinah, mawaddah, and warahmah family. This study employed a literature review method by analyzing 15 peer-reviewed journal articles indexed in SINTA 3–5 published between 2020 and 2025, focusing on premarital counseling and marriage readiness. The findings indicate that premarital counseling significantly contributes to improving couples’ understanding of marital roles, communication skills, readiness to face conflicts, and the internalization of religious and psychosocial values. These results suggest that premarital counseling plays a strategic role in strengthening marriage readiness and family resilience. Therefore, systematic and continuous implementation of premarital counseling is essential as a preventive effort to reduce marital conflict and divorce while fostering harmonious and resilient family life.